A thousand splendid suns - Hosseini, Khaled; Leoni, Atossa (New York : Simon & Schuster, 2007)
After more than two years on the bestseller lists, Khaled Hosseini returns with a beautiful, riveting, and haunting novel of enormous contemporary relevance. A Thousand Splendid Suns is a breathtaking story set against the volatile events of Afghanistan's last thirty years-from the Soviet invasion to the reign of the Taliban to post-Taliban rebuilding-that puts the violence, fear, hope and faith of this country in intimate, human terms. It is a tale of two generations of characters brought jarringly together by the tragic sweep of war, where personal lives-the struggle to survive, raise a family, find happiness-are inextricable from the history playing out around them. Propelled by the same storytelling instinct that made The Kite Runner a beloved classic, A Thousand Splendid Suns is at once a remarkable chronicle of three decades of Afghan history and a deeply moving account of family and friendship. It is a striking, heart wrenching novel of an unforgiving time, an unlikely friendship, and an indestructible love-a stunning accomplishment.
Downloadable audio file.
Title from: Title details screen.
Unabridged.
Duration: 11:43:00
Available to Vancouver Residents only.
Residents of other municipalities should check their local library.
Keywords: Families -- Fiction; Loss (Psychology) -- Fiction; Intergenerational relations -- Fiction; Afghanistan -- Fiction; Family chronicles; War fiction